The Concept of 'Aqal in the Al-Qur'an - Adib Fattah Suntoro; Amir Sahidin (University of Darussalam Gontor, Indonesia, 2021)
Discourse on the meaning of 'aqal is not as simple as it seems. The commonly translated 'aqal' pronunciation of